The Glare Effect Test and the Impact of Age on Luminosity Thresholds - Facchin, Alessio; Daini, Roberta; Zavagno, Daniele (Frontiers in Psychology, 2017)
The Glare Effect is an illusion in which a white region appears self-luminous when surrounded by linearly decreasing luminance ramps. It has been shown that the magnitude of the luminosity effect can be modulated by manipulating the luminance range of the gradients. In the present study we tested the thresholds for the glare effect on two groups of adults: young (20-30 years old) and elderly (60-75 years old). Purpose of our perspective study was to test the possibility of transforming the glare effect into a test that could easily measure thresholds for luminosity and discomfort glare. The Glare Effect Test (GET) consisted in 101 printed cards that differed from each other for the range of luminance ramps. Participants were assessed with GET and a battery of visual tests: visual acuity, contrast sensitivity, illusion of length perception, and Ishihara test. Specifically in the GET, participants were required to classify cards on the basis of two reference cards (solid black-no gradient; full range black to white gradient). PSEs of the glare effect show no correlation with the other visual tests, revealing a divergent validity. A significant difference between young and elderly group was found: contrary to our original expectations, luminosity thresholds for elderly were higher than those for young, suggesting a non-direct relationship between luminosity perception and discomfort glare.